The new "Europe of security": Elements for a European white paper on security and defence - Annegret Bendiek (Stiftung Wissenschaft und Politik (SWP), 2017)
With the Estonian Presidency of the EU Council from July until December 2017, the main topics will be digitalization and 'a safe and secure Europe'. The Council Presidency will, therefore, be tackling Europe's major challenges. At the same time, it can make use of a wide-open window of opportunity, since the governments of the EU Member States are more willing than ever to consider deepening European foreign and security policy. The issue of security has also been a constant concern for the Commission since the beginning of its term - from President Juncker's Political Guidelines in July 2014 to his most recent State of the Union Address in September 2016. Politics and society support a 'Europe of Security' based on three major projects of current European policy: a security union, a defence union and close cooperation between NATO and the EU. When protecting critical infrastructures, i.e. cybersecurity, these projects merge. All three should be given a shared strategic vision in an overarching White Paper.
Keywords: 320